Indonesia’s Bilateral Health Diplomacy in Building National Pharmaceutical Resilience - Sulastri Sulastri; Wachyu Sulistiadi (Health Notions, 2023)
The disruption of the global pharmaceutical supply chain due to the COVID-19 pandemic has placed the independence of pharmaceutical preparations as a priority in realizing national pharmaceutical resilience given the high dependence of the domestic pharmaceutical industry on imported raw materials. This study aims to determine the strategies and achievements of Indonesia's bilateral health diplomacy in meeting the national resource gap in the context of building pharmaceutical sector resilience. The research was conducted using a qualitative approach with a case study design by utilizing data obtained from literature studies. The results showed that Indonesia's bilateral health diplomacy through the making of bilateral health cooperation agreements, organizing business forums, and working visits to partner countries proved to be able to fill the gap in efforts to build national pharmaceutical resilience through strengthening pharmaceutical resources, implementing technology transfer, concrete business cooperation between pharmaceutical companies, and increasing foreign direct investment. However, diplomacy improvement and refinement of the achievements of bilateral health diplomacy need to be continued so that bilateral health diplomacy can provide real benefits for the development of national pharmaceutical security. Keywords: bilateral agreements; business forums; health diplomacy; pharmaceutical resistance; working visits